Mixture design of starchy substrates hydrolysis by an immobilized glucoamylase from Aspergillus brasiliensis. Issue 5 (3rd September 2018) - Almeida, Paula Zaghetto; Messias, Josana Maria; Pereira, Marita Gimenez; Pinheiro, Vanessa Elisa; Monteiro, Lummy Maria Oliveira; Heinen, Paulo Ricardo; Cardoso, George Cunha; Jorge, João Atílio; Polizeli, Maria de Lourdes Teixeira de Moraes
Abstract: Starch has great importance in human diet, since it is a heteropolymer of plants, mainly found in roots, as potato, cassava and arrowroots. This carbohydrate is composed by a highly-branched chain: amylopectin; and a linear chain: amylose. The proportion between the chains varies according to the botanical source. Starch hydrolysis is catalyzed by enzymes of the amilolytic system, named amylases. Among the various enzymes of this system, the glucoamylases (EC 3.2.1.3 glucan 1, 4-alpha-glucosidases) are the majority because they hydrolyze the glycosidic linkages at the end of starch chains releasing glucose monomers. In this work, a glucoamylase secreted in the culture medium, by the ascomycete Aspergillus brasiliensis, was immobilized in Dietilaminoetil Sepharose-Polyethylene Glycol (DEAE-PEG), since immobilized biocatalysts are more stable in long periods of hydrolysis, and can be recovered from the final product and reused for several cycles. Glucoamylase immobilization has shown great thermal stability improvement over the soluble enzyme, reaching 66% more activity after 6 h at 60 °C, and 68% of the activity after 10 hydrolysis cycles. A simplex centroid experimental mixture design was applied as a tool to characterize the affinity of the immobilized enzyme for different starchy substrates. In assays containing several proportions of amylose, amylopectin and starch, the glucoamylase from A. brasiliensis mainly hydrolyzed the amylopectin chains, showing to have preference by branched substrates.